Prevalence and molecular characteristics of polymyxin-resistant Enterobacterales in a Chinese tertiary teaching hospital - Xiao, Chenlu; Li, Xuming; Huang, Lianjiang; Cao, Huiluo; Han, Lizhong; Ni, Yuxing; Xia, Han; Yang, Zhitao (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Polymyxin-resistant Enterobacterales poses a significant threat to public health globally, but its prevalence and genomic diversity within a sole hospital is less well known. In this study, the prevalence of polymyxin-resistant Enterobacterales in a Chinese teaching hospital was investigated with deciphering of their genetic determinants of drug resistance. Methods Polymyxin-resistant Enterobacterales isolates identified by matrix-assisted laser desorption were collected in Ruijin Hospital from May to December in 2021. Both the VITEK 2 Compact and broth dilution methods were used to determine polymyxin B (PMB) susceptibility. Polymyxin-resistant isolates were further characterized by molecular typing using PCR, multi-locus sequence typing, and sequencing of the whole genome. Results Of the 1,216 isolates collected, 32 (2.6%) across 12 wards were polymyxin-resistant (minimum inhibitory concentration (MIC) range, PMB 4–256 mg/ml, and colistin 4 ≥ 16 mg/ ml). A total of 28 (87.5%) of the polymyxin-resistant isolates had reduced susceptibility to imipenem and meropenem (MIC ≥ 16 mg/ml). Of the 32 patients, 15 patients received PMB treatment and 20 survived before discharge. The phylogenetic tree of these isolates showed they belonged to different clones and had multiple origins. The polymyxin-resistant Klebsiella pneumoniae isolates belonged to ST-11 (85.72%), ST-15 (10.71%), and ST-65 (3.57%), and the polymyxin-resistant Escherichia coli belonged to four different sequence types, namely, ST-69 (25.00%), ST-38 (25.00%), ST-648 (25.00%), and ST-1193 (25.00%). In addition, six mgrB specific mutations (snp_ALT c.323T>C and amino acid change p.Val8Ala) were identified in 15.6% (5/32) of the isolates. mcr-1, a plasmid-mediated polymyxin-resistant gene, was found in three isolates, and non-synonymous mutations including T157P, A246T, G53V, and I44L were also observed. Discussion In our study, a low prevalence of polymyxin-resistant Enterobacterales was observed, but these isolates were also identified as multidrug resistant. Therefore, efficient infection control measures should be implemented to prevent the further spread of resistance to last-line polymyxin therapy.